Massachusetts Statewide Criminal Justice Guidelines Evaluation, 1979: Sentencing Data - Sparks, Richard F. ([Verlag nicht ermittelbar], 1984)
This data collection is the result of a project established to study the development, implementation, and use of statewide sentencing guidelines and to report on the perceptions of criminal justice system personnel and inmates regarding those guidelines. Funded by the National Institute of Law Enforcement and Criminal Justice, the project was carried out by the Rutgers University School of Criminal Justice from October 1978 to June 1981. Additional data produced by this project are contained in two other studies held by ICPSR: NEW JERSEY STATEWIDE CRIMINAL JUSTICE GUIDELINES EVALUATION, 1979 (ICPSR 7910) and NEW JERSEY STATEWIDE CRIMINAL JUSTICE GUIDELINES EVALUATION, 1980: INMATE SURVEY DATA (ICPSR 7911). The Massachusetts Sentencing Data contains information on a random sample of 1,440 convicted defendants sentenced in the Massachusetts Superior Court between November 1977 and October 1978. The sample represents approximately one-third of the actual number of defendants sentenced in the Massachusetts Superior Court during a one-year period. The cases were selected and coded by the Massachusetts Sentencing Guidelines project during 1979. Variables include information about each defendant's juvenile and adult criminal history, characteristics of the current offense, and the elements of the disposition of the current offense. Demographic data include defendant's age, sex, race, marital status, employment status, occupation, income, number of children, educational attainment, and drug and alcohol use history.